Dynamic RAM : technology advancements - Siddiqi, Muzaffer A. (Boca Raton, Fla. : CRC Press, 2013)
Dynamic RAM (DRAM) has wide applications in the computer industry, telecommunications, the military, and the space industry. This book presents an up-to-date account of the theory and design of DRAM, the workhorse of all semiconductor memories. It summarizes the development of and recent advances in manufacturing technology, generation by generation. The text also addresses DRAM cell development capacitor enhancement technologies, different types of leakages, and the circuit and technological aspects of the remedial measures taken--
1. Random access memories -- 2. DRAM cell development -- 3. DRAM technologies -- 4. Advanced DRAM cell transistors -- 5. Storage capacitor enhancement techniques -- 6. Advanced DRAM technologies -- 7. Leakages in DRAMs -- 8. Memory peripheral circuits.
Keywords: Semiconductor storage devices; Random access memory